PENGARUH KUALITAS PELAYANAN DI BOARDING GATE DAN FASILITAS RUANG TUNGGU TERHADAP KEPUASAN PENUMPANG DI BANDAR UDARA ABDUL RACHMAN SALEH MALANG - Qonitah Rahmawati (Pusat Riset dan Inovasi Nasional, 2022)
Along with the times and the rapid population growth in Indonesia, the needs of the diverse population will also increase, not least in the field of transportation. Transportation is a very important need for people in this era, the reason is because transportation is very helpful and makes it easier for users, especially air transportation. This study aims to examine and determine the effect of the variable quality of service and waiting room facilities partially or simultaneously on passenger satisfaction at Abdul Rachman Saleh Airport Malang. Using quantitative methods with explanatory research with a sample of 75 passengers using Abdul Rachman Saleh Airport Malang. Data collection was carried out by distributing questionnaires offline and online using a google form, which was then processed through SPSS version 21. As a result of the research, the variables of service quality and waiting room facilities have partial or simultaneous effect on passenger satisfaction at Abdul Rachman Saleh Airport, Malang. Based on the results of data analysis, the quality of boarding gate services has a positive and significant effect on passenger statisfaction at Abdul Rachman Saleh Airport, Malang.